Localized IRES-Dependent Translation of ER Chaperone Protein mRNA in Sensory Axons - Pacheco, Almudena (Public Library of Science, 2012)
Transport of neuronal mRNAs into distal nerve terminals and growth cones allows axonal processes to generate proteins autonomous from the cell body. While the mechanisms for targeting mRNAs for transport into axons has received much attention, how specificity is provided to the localized translational apparatus remains largely unknown. In other cellular systems, protein synthesis can be regulated by both cap-dependent and cap-independent mechanisms. The possibility that these mechanisms are used by axons has not been tested. Here, we have used expression constructs encoding axonally targeted bicistronic reporter mRNAs to determine if sensory axons can translate mRNAs through cap-independent mechanisms. Our data show that the well-defined IRES element of encephalomyocarditis virus (EMCV) can drive internal translational initiation of a bicistronic reporter mRNA in distal DRG axons. To test the potential for cap-independent translation of cellular mRNAs, we asked if calreticulin or grp78/BiP mRNA 5′UTRs might have IRES activity in axons. Only grp78/BiP mRNA 5′UTR showed clear IRES activity in axons when placed between the open reading frames of diffusion limited fluorescent reporters. Indeed, calreticulin’s 5′UTR provided an excellent control for potential read through by ribosomes, since there was no evidence of internal initiation when this UTR was placed between reporter ORFs in a bicistronic mRNA. This study shows that axons have the capacity to translate through internal ribosome entry sites, but a simple binary choice between cap-dependent and cap-independent translation cannot explain the specificity for translation of individual mRNAs in distal axons.